TUGAS DAN KEWENANGAN PEMERINTAH DAERAH JAWA BARAT TERHADAP PENANGANAN PENCEMARAN DAERAH ALIRAN SUNGAI CITARUM: Duties And Authorities of The West Java Provincial Government in Handling Pollution of The Citarum River Basin - Bima Indraswara Djati; Dhany Rahmawan (Faculty of Law, Universitas Trisakti, 2025)
The Citarum River Basin (DAS Citarum) is a strategic water resource that supports domestic, industrial, and agricultural needs in West Java. However, pollution caused by unmanaged domestic, industrial, and agricultural waste has significantly deteriorated the river’s water quality. This article examines the duties and authorities of the West Java provincial government in addressing pollution in the Citarum River Basin. Based on Law Number 23 of 2014 concerning Regional Government, the provincial government holds key responsibilities, including supervision, environmental management, and law enforcement against polluters. In response, a specific Governor Regulation was issued to enhance pollution control in the Citarum River. This study employs a normative juridical method with an analytical-deductive approach. The research findings reveal that although the government has broad authority, implementation remains hampered by weak inter-sectoral coordination, limited resources, and low public awareness. These issues hinder the effectiveness of existing policies. Therefore, strengthening legal frameworks, improving public education, and fostering cross-sectoral collaboration are essential to enhance the success of pollution control programs in the region. This study highlights the need for active stakeholder engagement and integrated efforts to restore the environmental function of the Citarum River Basin.